2016
DOI: 10.17014/ijog.3.2.77-94
|View full text |Cite
|
Sign up to set email alerts
|

Volcanostratigraphic Sequences of Kebo-Butak Formation at Bayat Geological Field Complex, Central Java Province and Yogyakarta Special Province, Indonesia

Abstract: -Bayat Complex is usually used as a work field for students of geology and other geosciences. The study area is located in the southern part of the Bayat Complex. Administratively, it belongs to Central Java Province and Yogyakarta Special Province. The lithology of Bayat is very complex, composed of various kinds of igneous, sedimentary, metamorphic, and volcanic rocks. Most of previous researchers interpreted Bayat as a melange complex constructed within a subduction zone. Kebo-Butak is one of formations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Parallel Nikol of lithic tuffs exposed at Cengkehan; from the upper right counterclockwise are C01A, C01B, C02, and C03. It shows lithic fragments with irregular shapes but some featuring circle shape, vuggy and cementing with silicic materials Based on the regional geology by the previous studies, reported Kebo-Butak Formation aged Late Oligocene to Early Miocene, was exposed at Tegalrejo-Gedangsari (Gunungkidul; Mulyaningsih, 2016) and Gunung Kebo and Butak (Bayat, Klaten;Surono et al, 1992). It consisted of submarine volcaniclastic deposits associated with calcareous sediments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parallel Nikol of lithic tuffs exposed at Cengkehan; from the upper right counterclockwise are C01A, C01B, C02, and C03. It shows lithic fragments with irregular shapes but some featuring circle shape, vuggy and cementing with silicic materials Based on the regional geology by the previous studies, reported Kebo-Butak Formation aged Late Oligocene to Early Miocene, was exposed at Tegalrejo-Gedangsari (Gunungkidul; Mulyaningsih, 2016) and Gunung Kebo and Butak (Bayat, Klaten;Surono et al, 1992). It consisted of submarine volcaniclastic deposits associated with calcareous sediments.…”
Section: Discussionmentioning
confidence: 99%
“…It consisted of submarine volcaniclastic deposits associated with calcareous sediments. The distinguished volcanic rocks were basalt (as sill, dykes and lava), black colour of rich-glass crystal tuffs, layered yellowish to creamy crystal tuff, and laminated light grey dacitic tuff (Mulyaningsih, 2016). That s why, Surono (2009) interpreted Kebo-Butak Formation as deep-sea turbiditic sequence affected by volcanic origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Penelitian terfokus pada Satuan Lava Bantal yang terdapat di Desa Jarum, Kecamatan Bayat, Kabupaten Klaten, Provinsi Jawa Tengah. Lokasi ini berada di sebelah utara Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta Lava Bantal Nampurejo memiliki struktur bantal dan memiliki komposisi basalt (Surono, 2008) dan menurut Mulyaningsih (2016) terjadi dua proses vulkanisme di lokasi penelitian yang mengakibatkan terendapkannya lava bantal dan endapan vulkanik feldspar. Penelitian ini bertujuan untuk mengetahui linkungan tektonik lava bantal.…”
unclassified